Prostitution policy: revolutionizing practice through a gendered perspective - Kuo, Lenore (New York University Press, 2002)
Introduction. -- Contextualizing the discussion : feminism and policy analysis -- A sexually charged context, the feminist "sex wars," and prostitution defined -- The intrinsic character of heterosexual activity and prostitution -- Sexuality and prostitution as conceptual constructs -- The practice of heterosexuality and heterosexual prostitution -- The "ideal" character of heterosex/intercourse and prostitution -- Evolving a policy legal status -- The feminist debate -- Prostitution solution : policy recommendations.